A large-scale genome-wide association and meta-analysis identified four novel susceptibility loci for leprosy - Zhenzhen Wang (Nature Portfolio, 2016)
Previous studies have shown genetic associations between leprosy and 18 different genes/loci. Here, Wang and colleagues perform genome-wide association study in Han Chinese leprosy patients and describe four novel loci to be associated to the disease.